Modeling of Dynamic Response of Beam-Type Vibration Absorbing System Excited by a Moving Mass - Putra, Azma; Susilo, Sidik (Praise Worthy Prize, 2013)
A numerical simulation to calculate the dynamic response of a beam attached with beam vibration absorber through a viscoelastic layer subjected to a moving load is presented in this paper. The mathematical model is formulated by using Euler-Bernoulli theory to calculate the vertical response of the system. The ffict of the inertia of the moving load is included in the model to study its effect on the beam response at the mid span. The viscoelastic layer is introduced as uniformly distributed stiffness and damping and the concept of mixed damping ratio is implemented which allows the system to be modeled for dffirent rigidity ratio. The response is calculated using time integration method for dffirent moving mass inertia, rigidity ratio of the beams and the stffiess and damping of the visco-elastic layer. The effect is investigated for dffirent values of mass and speed of the moving load